Fabrication and electrical properties of PC-PNZT-PVDF-GO composites - Nittaya Jaitanong (2018)
© 2017 Taylor & Francis Group, LLC. The objectives of this research are to fabricate and investigate new smart composites for the sensing and actuation applications in civil engineering. The fabrication and properties of cement-based piezoelectric ceramic composites are emphasized. However, cement-based piezoelectric composites are still difficult to obtain great electrical properties due to the evidence of some pores in the composites. Therefore, a novel approach to effectively improve their polarization of piezoelectric ceramic is to add a semiconductor (graphene oxide) and an insulator (polyvinylidene fluoride) phases between piezoelectric particles by the introduction of a small volume fraction of a third phase. Microstructure of the new composites was investigated using Scanning electron microscope (SEM). Dielectric permittivity and ferroelectric properties were then investigated.